Performance of Altriset™ (Chlorantraniliprole) Termiticide Against Formosan Subterranean Termites, Coptotermes formosanus Shiraki, in Laboratory Feeding Cessation and Collateral Transfer Trials, and Field Applications - Gold, Roger E (Sociobiology, 2014)
Chlorantraniliprole represents the first compound to be registered as a termiticide by the Environmental Protection Agency (EPA) in over a decade. This novel termiticide is currently registered as a ‘reduced-risk pesticide’ by the EPA. Laboratory and field trials were conducted to quantify mortality of Formosan subterranean termites (FST), Coptotermes formosanus Shiraki resulting from chlorantraniliprole treated soil, the degree to which the termites curtail feeding intensity post-exposure to chlorantraniliprole treated soil, collateral transfer of chlorantraniliprole among nest mates, and the effectiveness of chlorantraniliprole as a remedial treatment against structural infestations of FST. Termites which were exposed to chlorantraniliprole treated soil consumed significantly less paper than unexposed FST. The mean percent mortality of those termites exposed to chlorantraniliprole treated soil was significantly greater than that of unexposed FST. Depending on donor:recipient ratios, the mean mortality of recipients ranged from 14.65 – 90.00 % in the collateral transfer trials. There was a positive correlation between increased donor density and recipient mortality. Through 24 mo post-treatment, 27.3% of the structures which were treated in field trials were observed to have infestations of termites that required re-treatment; however, no active FST were observed to be infesting any of the structures during the 30 and 36 month post-treatment inspections. Additionally, a novel scoring rubric was developed that will allow standardization of field study sites with respect to dissimilarity in site variables, and will allow for more consistent comparison of resultsacross disparate field experiments. An explanation for the lack of successful remediation of many of the structures involved in the field trial is proposed and is based on our novel scoring system.